Activation of the immune response by cytokines and its effect on tumour cells: a mathematical model. (30th June 2018) - CH-Chaoui, Mohamed; Eladdadi, Amina; Mokni, Karima
Abstract: In this paper, we present a mathematical model at the cellular level of the tumour–immune competition mediated by the cytokines. The model consists of a system of nonlinear differential equations describing the intracellular interactions between the tumour and the immune cells in the presence of the cytokines. A detailed phenomenological description of the model based on the kinetic theory for active particle approach is carried out to formulate the model. Well-posedness is presented to establish local and global existence. Numerical simulations are addressed to show how initial conditions and model parameters influence the output of the model. Under a suitable choice of the model's key parameters and the cytokines' initial activation levels, the simulation results show that the activated immune system is able to achieve a total elimination of the cancer cells.